2005
DOI: 10.1111/j.1365-2141.2005.05493.x
|View full text |Cite
|
Sign up to set email alerts
|

The absence of CD56 on malignant plasma cells in the cerebrospinal fluid is the hallmark of multiple myeloma involving central nervous system

Abstract: SummaryBy immunohistochemistry, the CD56-positive myeloma cells were detected in three (38%) bone marrow (BM) and one (13%) cerebrospinal fluid (CSF) samples from eight patients with multiple myeloma involving the central nervous system (CNS MM). Of the three patients with CD56-positive BM myeloma cells, two had CSF myeloma cells negative for CD56. In a control cohort of 84 MM patients without CNS involvement, the BM myeloma cells were CD56-positive in 68 (80%) cases (P < 0AE0001). The prevalence of CD56-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 14 publications
2
29
2
Order By: Relevance
“…3,10,17 Several observation are in agreement with a possible role of p53 deletions, 4 high nuclear accumulation of the p53 protein, 34 and del (17p13). 10 An interesting report by Gozzetti et al 16 showed the possible involvement of t (11;14), which seems to be associated with standard risk, but also with high risk in the presence of plasma cell leukemia.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…3,10,17 Several observation are in agreement with a possible role of p53 deletions, 4 high nuclear accumulation of the p53 protein, 34 and del (17p13). 10 An interesting report by Gozzetti et al 16 showed the possible involvement of t (11;14), which seems to be associated with standard risk, but also with high risk in the presence of plasma cell leukemia.…”
supporting
confidence: 65%
“…In a previous clinical study concerning either cases of CNS-MM or other extramedullary sites of localization of MM, immunocytochemical techniques were applied, with the evidence of substantial lack of CD56 expression. 21,[34][35][36][37][38][39][40] The hypothesis that CD56 down-regulation might favor the migration of MM plasma cells from the bone marrow was put forward.…”
mentioning
confidence: 99%
“…Over 70% of patients with MM may have positive CD56 antigen, indicating either aggressive or indolent form of myeloma, but its absence indicates only aggressive myeloma phenotypes [39,40]. Down regulation of CD56 antigen is considered responsible for myeloma cells escaping from bone marrow [41]. In a case series of eight patients with LMM, myeloma cells were negative for CD56 in both bone marrow and CSF in five patients (62.5%) [41].…”
Section: Blood Biomarkersmentioning
confidence: 98%
“…2 Approximately 1% of MM patients develop CNS myeloma. 3 Myelomatous meningitis may originate in the plasma cells that spread to the meninges through thin walled microscopic veins in the arachnoid membrane 3,4 or MM may disseminate via circulating lymphocytes that may be progenitors of myeloma cells. 5 Meningeal involvement in MM may arise in the absence of circulating plasma cells 6 .…”
Section: Discussionmentioning
confidence: 99%